Some Issues of E-pedagogy: A Case Study at University of Education (VNU-UED) - Cường, Tôn Quang; Chung, Phạm Kim; Mai, Đào Thị Hoa (VNU Journal of Science: Education Research, 2014)
Abstract: In 2010 the first e-learning courses had been held to train teachers (Bachelor level) and the educational managers (Master degree) at the University of Education, Vietnam National University, Hanoi (VNU-UED). The application of the non-traditional mode in this teaching approach has created a number of changes in deploying the pedagogial activities and learning environment. These courses were designed in the direction of supplying the contents of knowledge and organizing the teaching activities in the new way in order to raise the output quality and develop the professional skills for the learners at UED. This research was conducted to make recommendations in the pedagogical aspect on how to get access to the design and organization of e-learning, to make clear a number of fundamental principles and to explain the phenomenon of E-pedagogy concept based on the previous classic teaching theories. Keywords: E-pedagogy, E-learning, learning theories, technological acceptance.